Test–retest reliability of the Epworth Sleepiness Scale in clinical trial settings. (20th September 2021) - Rosenberg, Russell; Babson, Kimberly; Menno, Diane; Morris, Susan; Baladi, Michelle; Hyman, Danielle; Black, Jed
Summary: The present analysis examined the test–retest reliability of the Epworth Sleepiness Scale in participants with excessive daytime sleepiness associated with narcolepsy or obstructive sleep apnea in three clinical trials. Intraclass correlation coefficient estimates for Epworth Sleepiness Scale scores from two solriamfetol 12‐week placebo‐controlled trials (one narcolepsy, one obstructive sleep apnea) and one long‐term open‐label extension trial (narcolepsy or obstructive sleep apnea) were calculated using postbaseline time‐point pairs for the overall population in each trial, by treatment, and by primary obstructive sleep apnea therapy adherence. In the 12‐week narcolepsy trial, intraclass correlation coefficients (95% confidence intervals) were 0.83 (0.79, 0.87) for weeks 4 and 8 ( n = 199), 0.87 (0.83, 0.90) for weeks 8 and 12 ( n = 196), and 0.81 (0.76, 0.85) for weeks 4 and 12 ( n = 196). In the 12‐week obstructive sleep apnea trial, intraclass correlation coefficients (95% confidence intervals) were 0.74 (0.69, 0.78) ( n = 416), 0.80 (0.76, 0.83) ( n = 405), and 0.74 (0.69, 0.78) ( n = 405), respectively. In the open‐label extension trial, intraclass correlation coefficients (95% confidence intervals) were 0.82 (0.79, 0.85) for weeks 14 and 26/27 ( n = 495), 0.85 (0.82, 0.87) for weeks 26/27 and 39/40 ( n = 463), and 0.78 (0.74, 0.81) for weeks 14 and 39/40 ( n = 463). Placebo/solriamfetol treatment or adherence to primary obstructive sleep apnea therapy did not affect reliability. In conclusion, across three large clinical trials of participants with narcolepsy or obstructive sleep apnea, Epworth Sleepiness Scale scores demonstrated a robust acceptable level of test–retest reliability in evaluating treatment response over time.